In vivo evidence that secretion of HLA‐G by immunogenic tumor cells allows their evasion from immunosurveillance. Issue 9 (7th April 2014) - Loumagne, Laure; Baudhuin, Jeremy; Favier, Benoit; Montespan, Florent; Carosella, Edgardo D.; Rouas‐Freiss, Nathalie
<x xml:space="preserve">Abstract</x> Human leukocyte antigen‐G (HLA‐G) expression by tumors has been evidenced in numerous malignancies in association with poor prognosis and resistance to immunotherapy in humans. Particularly, soluble form of HLA‐G was measured at high concentrations in malignant effusions and plasma from cancer patients, and inhibits antitumor immune cells in vitro through interaction with immunoglobulin‐like transcript (ILT) receptors. Nevertheless, in vivo study demonstrating that HLA‐G secretion by tumor cells allows their escape from immunosurveillance remained to be established. Despite nondescribed murine homolog, direct functional interaction of HLA‐G with murine paired immunoglobulin‐like receptor (PIR)‐B, ortholog of human ILT receptors, enables to investigate its role in vivo. Immunocompetent mice were injected either with syngeneic tumor cells co‐expressing HLA‐G5, the main soluble HLA‐G isoform, and the conformation stabilizer human β2‐microglubulin (hβ2m), or with hβ2m+HLA‐G5− tumor cells. hβ2m expressed at both tumor cell surface acted as a tumor antigen triggering a specific humoral response. Interestingly, although hβ2m+HLA‐G5− tumors were rejected, secreted HLA‐G5 provided hβ2m+HLA‐G5+ tumors a protection against hβ2m‐elicited immune rejection, enabling such immunogenic tumors to grow similarly to a poorly immunogenic tumor. HLA‐G5 tumor expression was associated with local and peripheral immunosuppression, characterized by dampened anti‐hβ2m B‐cell response, quantitative and functional T‐and B‐cell defects, accumulation of myeloid‐derived suppressor cells able to inhibit T‐cell proliferation and reduced T‐ and B‐cell tumor infiltrate. Our study provides the first in vivo proof that soluble HLA‐G counteracts tumor rejection and reinforces the importance to consider HLA‐G as a promising target to optimize current cancer immunotherapies.